Population, Ethnicity and Locality: A Study of Dehzado Records of the 1881 Census of Baroda State. (April 2017) - Shah, A.M.; Lobo, Lancy; Kumar, Shashikant
At the Census of India, 1881, the former princely state of Baroda published data for every village and town, called Dehzado. After presenting the general demography of Baroda state, this article presents an analysis of data on caste, tribe and religion. It provides classification of villages and towns by the number of castes and tribes found in them, and discusses the issues posed by them, especially the issue of single-caste villages. This article describes the horizontal spread of various castes, tribes and religious minorities and points out its implications. In the end, it discusses the problem of urbanisation, classifying the towns by ethnic groups found in them.